Kreativitas Pembuatan Lagu Anak Tematik Berbasis Video Interaktif Sebagai Inovasi Pembelajaran Seni Musik di Sekolah Dasar - Zakarias Aria Widyatama Putra; Mastri Dihita Sagala (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Creativity can produce a product. The product of creating or making interactive video-based thematic children's songs answers the challenges and civilization regarding learning innovation in Indonesia, especially in the 21st century, which in this case is the research objective. In addition to answering the challenges of interactive videos made can also be a solution to the sense of disinterest of elementary school students in learning materials, especially music. The resulting song is intended for elementary school students in phase A (in the independent curriculum) or in grades 1-3. The method to uncover this research used a descriptive qualitative method with a case study approach. Data analysis uses data collection from primary sources such as full scores of thematic children's songs, interactive videos, inhibition during PGSD music education learning, and interviews with students. Furthermore, the data collected is reduced according to the topic of the article, presented, and sought for red threads or conclusions. Validated results that the process and results of creativity in making thematic children's songs based on interactive videos can be used as an innovation in music learning at the elementary school level.